FORMACIÓN DE PORO EN MEMBRANA CELULAR POR MEDIO DE LA PEQUEÑA GLICOPROTEÍNA DE SECRECIÓN DEL VIRUS DE EBOLA ZAIRE - Vargas Alejo, Nury Esperanza; Facultad de Ciencias y Educación, Proyecto Curricular de Licenciatura en Química, Universidad Distrital Francisco José de Caldas, Bogotá D.C. (2004)
One of the pathogens able to produce haemorrhagic fevers is Ebola virus, classified in the Filovirideae family, which has four sub-types, the most analyzed of which is the Zaire sub-type. The genome of this virus contains the information of seven structural proteins and one non-structural  glycoprotein called Small Secretion Glycoprotein of the Ebola Zaire virus (SSGP). Using bioinformatic tools and previous studies about the Ebola virus, we predicted the tertiary structure of the small secretion glycoprotein (SSGP EBO-Z), and based on that, we generated a model to explain the mechanism by which the virus enters host cells, where receptors of the cell surface play an important role. This provided an explanation for the symptoms and pathological damage found in patients.